Politics at Work - Colonnelli, Emanuele; Neto, Valdemar Pinho; Teso, Edoardo (American Economic Review, 2025)
We study how individual political views shape firm behavior and labor market outcomes using new microdata from Brazil. We first show that business owners are considerably more likely to employ copartisan workers. This phenomenon is in part driven by the overlapping of political and social networks. Multiple tests—surveys, event studies, analyses of wage premia and promotions within the firm, and a field experiment—further highlight how business owners’ political preferences directly influence firms’ employment decisions. A channel of political discrimination appears more relevant than one of political quid pro quo between firms and politicians. (JEL C93, D22, D72, J23, M51, O17, Z13)